Literasi Matematika Tahap Merumuskan Masalah Secara Matematis Siswa Kemampuan Tinggi dalam Memecahkan Masalah Matematika Kelas VIII - Khanifah Khanifah; Sutrisno Sutrisno; FX. Didik Purwosetiyono (Universitas Indraprasta PGRI, 2019)
The purpose of this study is to determine the level of mathematical literacy of high ability students in solving mathematics problems in class VIII SMP. The study was conducted at SMP Negeri 3 Purwodadi in the 2018/2019 school year. This research is a descriptive qualitative research. Data collection is done by tests, interviews, and documentation. The research subjects were chosen by three students, all of whom are students with high literacy mathematical abilities. The results showed that the mathematical literacy process of students at the stage of formulating mathematical problems was identifying the mathematical aspects of a problem context in real life and identifying known variables; determine mathematical models and simplify problems; and determine aspects of mathematical concepts, facts or procedures of a problem.